2011
DOI: 10.1186/1477-7525-9-1
|View full text |Cite
|
Sign up to set email alerts
|

Combined life satisfaction of persons with stroke and their caregivers: associations with caregiver burden and the impact of stroke

Abstract: BackgroundLittle is known about the life satisfaction of the person with stroke combined with their caregiver, i.e. the dyad, despite the fact that life satisfaction is an important rehabilitation outcome. The aim of this study was to describe the dyads combined life satisfaction and to understand this in relationship to the perceived impact of stroke in everyday life and caregiver burden.MethodsIn this cross-sectional study, the life satisfaction of persons and their informal caregivers was measured in 81 dya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
136
1
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(151 citation statements)
references
References 42 publications
11
136
1
3
Order By: Relevance
“…These findings are in accordance with a Swedish cross-sectional study that investigated burden and life satisfaction in caregivers of patients with stroke (Bergstrom et al, 2011). This is the first study to investigate caregiver burden and life satisfaction simultaneously after severe TBI.…”
Section: Correlation Between Caregiver Burden and Life Satisfactionsupporting
confidence: 75%
See 3 more Smart Citations
“…These findings are in accordance with a Swedish cross-sectional study that investigated burden and life satisfaction in caregivers of patients with stroke (Bergstrom et al, 2011). This is the first study to investigate caregiver burden and life satisfaction simultaneously after severe TBI.…”
Section: Correlation Between Caregiver Burden and Life Satisfactionsupporting
confidence: 75%
“…Livingston et al, 2010a), which was consistent with the findings of a cross-sectional study (Kreutzer et al, 2009). One investigation of caregiver burden and life satisfaction in caregivers of patients with stroke reported that a lower life satisfaction was associated with higher burden (Bergstrom et al, 2011).…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…Notre taux de participation estimé est de 26,5 %, et donc similaire à celui d'autres études (27 %) [38]. L'envoi des demandes de consentement par voie postale réduit inévitablement le taux de réponses.…”
Section: Limitesunclassified